DESCRIPTION OF ORAL CAVITY MICROBIAL CULTURE IN DENTAL CARIES SUFFERERS - Aminah Aminah; Firda Azizah; Indra Setyawati (Dentino: Jurnal Kedokteran Gigi, 2024)
Background: Dental caries is one of the most common oral health problems worldwide, affecting 573 million children and 2.5 billion adults. Dental caries is a disease that attacks the hard tissues of the tooth, such as cementum, dentin, and enamel. This causes bacterial invasion, pulp death, and spread of infection to periapical tissues, which can cause pain. Purpose: The purpose of this study was to determine the microbial culture picture of the oral cavity of patients with dental caries. Methods: This research is descriptive and the samples in this study amounted to 7 samples of patients with dental caries at Dr. Sitanala Hospital, Tangerang City. The sampling technique in this study used purposive sampling technique. Results: The results of this study found 1 sample (14.3%) of Candida albicans fungus in fungal culture. In addition, 9 samples (64.3%) of Staphylococcus Sp. bacteria, 3 samples (21.4%) of Klebsiella Sp. bacteria, and 2 samples (14.3%) of Bacillus Sp. bacteria were found in the bacteria culture. Conclusion: It has been proven that the oral cavity of dental caries sufferers contains various kinds of microbes, such as the fungus Candida albicans, the bacteria Staphylococcus Sp., the bacteria Klebsiella Sp., and the bacteria Bacillus Sp..